'Sacrificial' supramolecular assembly and pressure-induced polymerization: toward sequence-defined functionalized nanothreads. Issue 42 (8th September 2020) - Gerthoffer, Margaret C.; Wu, Sikai; Chen, Bo; Wang, Tao; Huss, Steven; Oburn, Shalisa M.; Crespi, Vincent H.; Badding, John V.; Elacqua, Elizabeth
Abstract : Supramolecular synthons are exploited to synthesize –OH functionalized sp 3 -rich sequence-defined nanothreads using pressure-induced polymerization of a phenol:pentafluorophenol co-crystal. Abstract : Limited supramolecular strategies have been utilized to synthesize sequence-defined polymers, despite the prominence of noncovalent interactions in materials design. Herein, we illustrate the utility of 'sacrificial' aryl-perfluoroaryl supramolecular synthons to synthesize sp 3 -hybridized nanothreads from sp 2 -enriched reactants. Our strategy features A–B reactant pairs in the form of a phenol:pentafluorophenol co-crystal that is preorganized for an electronically-biased and sequence-defined polymerization. The polymerization, initiated at 12 GPa, affords an alternating copolymer featuring exogenous –OH functionalities. The external substitution is confirmed through IR spectroscopy. Importantly, the inclusion of the functional unit provides the first experimental glimpse at reaction mechanism: keto–enol tautomerization that can only occur during cycloaddition is observed through IR spectroscopy. Our approach realizes the first example of a functionalized nanothread and attains sequence definition through sacrificial supramolecular preorganization and presents a further approach for de novo design of complex nanothreads.